Sosyal a? analizi ve veri görselleştirme araçlarinin incelenmesi ve uygulamali karşilaştirilmasi - Bürhan, Yücel; Baykara, Muhammet; Daş, Resul (Institute of Electrical and Electronics Engineers Inc., 2017)
Social network analysis has become an important issue in recent years because of the development and use of social networks widespread. Almost any kind of data can be easily obtained as valuable information about actors from these data. In this study, general information about the most used social network analysis and visualization tools are given. The author-subject network that analyzed with the help of link estimation methods, the author-writer network showing the links between co-authors is drawn and displayed visually through four different social network analysis and visualization tools. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Big data; Data analysis; Social network; Social network analysis